An Academic Management Model of Small Schools towards Quality under the Office of the Basic Education Commission - Boonprasit, Yingluk; Masena, Chuankid; Singpan, Pongthorn (Ratchaphruek Journal, 2024)
The objectives of this research were: 1) To study the current conditions and needs of the academic management model; and 2) To develop the academic management model of small schools towards quality under the Office of the Basic Education Commission. The 242 school directors and head of academic group were the sample by using stratified random sampling methods, and 11 experts by purposive sampling. The research instruments used were the questionnaire had a reliability value of 0.87 and assessment form. The statistics used to analyze data were mean and standard deviation. The results of the research revealed that current conditions for an academic management model of small schools towards quality overall it is at a high level. The need to an academic management model of small schools towards quality overall it is at a high level. And an academic management model of small schools towards quality under the office of the basic education commission has 5 components: 1) principles, 2) objectives, 3) Methods, 4) Evaluation, and 5) Success Conditions. The model is appropriate at the highest level.